Photo-Regulation of Enzyme Activity: The Inactivation of a Carboligase with Genetically Encoded Photosensitizer Fusion Tags - Gerlach, Tim; Schain, Jendrik; Söltl, Simone; van Schie, Morten M. C. H.; Hilgers, Fabienne; Bitzenhofer, Nora L.; Drepper, Thomas; Rother, Dörte (Frontiers in Catalysis, 2022)
Genetically encoded photosensitizers are able to produce reactive oxygen species upon illumination and are exploited in a wide range of applications, especially in the medical field. In this work, we envisioned to further apply these genetically encoded photosensitizers for the light-dependent control of single enzymes in multi-step biocatalysis. One of the challenges in the application of several enzymes in a cascade is the unwanted cross-reactivity of these biocatalysts on reaction intermediates when all enzymes are simultaneously present in the reaction. As one strategy to address this issue, we investigated whether the introduction of genetically encoded photosensitizers as fusion tags would allow the selective inactivation of enzymes after successful transformation by simply turning on light. We tested five different photosensitizers as molecular biological fusion tags to inactivate the pyruvate decarboxylase variant E469G/W543H from Acetobacter pasteurianus. Dimeric photosensitizer tags, like the flavin-binding fluorescent proteins from Bacillus subtilis and Pseudomonas putida showed the tendency to form insoluble protein aggregates in combination with the tetrameric carboligase. Enzyme activity was, to some extent, retained in these aggregates, but the handling of the insoluble aggregates proved to be unfeasible. Monomeric photosensitizer tags appeared to be much more suitable when fused to the tetrameric enzyme. In the dark, the singlet oxygen producing protein (SOPP3)-tagged carboligase retained 79% of its activity as compared to the unfused enzyme. Upon blue light exposure, the SOPP3 tag showed the best specific inactivation and enabled complete inactivation of the carboligase within 30 min. SOPP3 is thus seen as a promising photosensitizer tag to be applied in future multi-step enzyme cascades to overcome the challenge of cross-reactivity.